Effect of drying profiles on surface structure changes of durum wheat pasta during the boiling process. (1st January 2023) - Ohmura, Masato; Matsumiya, Kentaro; Maeda, Tatsuro; Fujita, Akio; Hayashi, Yukako; Matsumura, Yasuki
Abstract: The aim of this study was to investigate the effect of different drying conditions on structural changes of durum wheat pasta during the boiling process. Boiled pasta samples with different drying conditions were evaluated under the same water absorption level in order to more consistently elucidate the effect on cooking properties. The evaluated properties were cooking loss, surface structure of the boiled pasta as observed by fluorescence microscopy, and surface roughness as assessed by a combination of laser microscopy and principal component analysis. Furthermore, the smoothness of samples was evaluated by sensory evaluation. Cooking loss was lower in VHT (very high temperature drying)- than in LT (low temperature drying)-boiled pasta. Structural observation of the pasta surface revealed that the swelling of starch granules was suppressed and a dense gluten network structure was maintained at the outer periphery in VHT-boiled pasta compared to LT-boiled pasta. Analysis of surface roughness indicated that the surface of VHT-boiled pasta was smoother than that of LT-boiled pasta, which was in agreement with the result of sensory evaluation of pasta smoothness. Highlights: Structural observation of boiled pasta with different drying conditions revealed differences in the outer periphery. Low temperature drying-boiled pasta demonstrated the highest cooking loss. Surface roughness of the boiled pasta decreased with increasing drying temperature. Results of laser microscopy analysis and sensory evaluation were consistent.